KINERJA GURU DITINJAU DARI PENGARUH LINGKUNGAN KERJA DAN PENGHARGAAN - Merry, Merry; Harapan, Edi; Rohana, Rohana (Jurnal Ilmiah Bina Edukasi, 2020)
This research aims to determine the effect of the work environment and rewards on teachers’s performance at SMPN 1 Indralaya. This research uses quantitative methods with correlational type of research. The research population was 45 people, namely the teachers at SMPN 1 Indralaya. The number of research samples were 40 people. The sampling technique in this study is simple random sampling. Data collection techniques using a questionnaire. Data were analyzed using simple linear regression test analysis techniques and multiple linear regression. Research results show that: (1) The work environment has no significant effect on the teachers’s performance at SMPN 1 Indralaya. (2) The rewards has a significant effect on the teachers’s performance at SMPN 1 Indralaya (3) Work environment and rewards together have a significant effect on the teachers’s performance at SMPN 1 Indralaya